2012
DOI: 10.1089/jpm.2011.0505
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Goals-of-Care Video for Elderly Patients Admitted to Skilled Nursing Facilities

Abstract: Objective: To determine the impact of a video on preferences for the primary goal of care. Design, subjects, and intervention: Consecutive subjects 65 years of age or older (n = 101) admitted to two skilled nursing facilities (SNFs) were randomized to a verbal narrative (control) or a video (intervention) describing goals-of-care options. Options included: life-prolonging (i.e., cardiopulmonary resuscitation), limited (i.e., hospitalization but no cardiopulmonary resuscitation), or comfort care (i.e., symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 23 publications
5
100
0
Order By: Relevance
“…General scope of care options: life-prolonging (ie, CPR and life-sustaining treatments), limited interventions (ie, hospitalization with limitations in the extent of medical intervention), or comfort care (ie, symptom relief) 34,35 Role of artificial nutrition and hydration Role of hospitalization and/or outpatient services such as hospice 11 Role of CPR, including recommending for or against this procedure 36 Table 2 provides examples for talking with older adults and translating preferences into current medical care plans, such as CPR directives, do-not-resuscitate orders, and out-of-hospital medical orders. Specifically, clinicians can use POLST forms to translate ACP preferences into medical orders, including CPR, scope of treatment, artificial nutrition by tube, and, in some states, antibiotic use, based on conversations with patients or surrogates.…”
Section: Translating Preferences Into Medical Care Plansmentioning
confidence: 99%
See 1 more Smart Citation
“…General scope of care options: life-prolonging (ie, CPR and life-sustaining treatments), limited interventions (ie, hospitalization with limitations in the extent of medical intervention), or comfort care (ie, symptom relief) 34,35 Role of artificial nutrition and hydration Role of hospitalization and/or outpatient services such as hospice 11 Role of CPR, including recommending for or against this procedure 36 Table 2 provides examples for talking with older adults and translating preferences into current medical care plans, such as CPR directives, do-not-resuscitate orders, and out-of-hospital medical orders. Specifically, clinicians can use POLST forms to translate ACP preferences into medical orders, including CPR, scope of treatment, artificial nutrition by tube, and, in some states, antibiotic use, based on conversations with patients or surrogates.…”
Section: Translating Preferences Into Medical Care Plansmentioning
confidence: 99%
“…ACP Decisions (http://www.acpdecisions.org/) presents ACP videos describing how overall goals of care, CPR, and mechanical ventilation can influence patients' and surrogates' preferences for end-of-life care. 35,44 The Conversation Project (http://theconversationproject.org/) 45 provides a written toolkit with values-based questions to help individuals start ACP conversations. The GO WISH Card Game, 46 a set of cards that describe potential quality-of-life values, may facilitate conversations among older adults with cognitive impairment.…”
Section: New Patient-centered Advance Care Planning Toolsmentioning
confidence: 99%
“…Patients exposed to video decision support tools had a greater likelihood to choose comfort goals (9), greater likelihood to complete advance directive documentation (10), and were less likely to opt for cardiopulmonary resuscitation (11). A randomized controlled trial of cancer patients found that an educational video on cancer pain improved outcomes associated with the Brief Pain Inventory and the Patient Pain Questionnaire (12).…”
Section: Introductionmentioning
confidence: 99%
“…Fourteen ACP stakeholders (three surgeons, two patient family advocates, two health services researchers, four palliative care clinicians and/or researchers, one medical film-maker, one patient-centered outcomes researcher and one patient safety and quality researcher) met to review a representative sample of seven ACP videos selected from published studies,30 websites31 or YouTube 4. Using design-thinking techniques,32 stakeholders identified important video elements to be: (1) patient-centered videos that feature personal stories delivered by ‘real’ patients and families; (2) a decision framework that emphasises and elicits ‘how people want to live’ rather than the treatments they want or do not want and (3) ‘upbeat’ music (where upbeat music was highly linked to increased engagement).…”
Section: Methodsmentioning
confidence: 99%